Acceptance of mobile English learning among college students in Henan - Xiao, Qiong; Ruey Shing, Soo; Lv, Yu (International Journal of Evaluation and Research in Education (IJERE), 2025)
The portability of smartphones offers tremendous potential for language learning. However, the willingness to accept and the practical adoption of mobile learning in English study among college students from Henan, China requires deeper exploration, due to the lower digital competency and limited usage of digital tools of English teachers in Henan, China. Targeted at the college students from Henan, this research intends to investigate factors influencing their intention to adopt mobile apps in learning English by conducting a quantitative study within the framework of modified technology acceptance model (TAM) model. Purposive sampling method was used and online questionnaire was administered among 511 college students with mobile English learning experiences from one comprehensive university in Henan and data were analyzed via SPSS and structural equation modelling (SEM). The key findings include: i) social influences (SI), perceived usefulness (UF), and perceived enjoyment (PEEN) significantly impact students’ intention to adopt mobile English learning; ii) SI affect students’ intention via the mediator of UF; and iii) perceived ease of use (EOU) does not significantly impact students’ intention. This research highlights the role of teachers’ influences in students’ adoption of mobile English learning and emphasizes the need for further improvement in mobile apps design to facilitate the learning experiences.